Контроль площ та стану озимих культур за допомогою знімків MODIS/TERRA та SPOT XI (на прикладі Київської області) - Лялько, В.І.; Сахацький, О.І.; Жолобак, Г.М.; Греков, Л.Д. (Видавничий дім "Академперіодика" НАН України, 2007)
The research of the possibility to use autumn MODIS/TERRA images for the determination of the area and growth conditions of winter crops in the Kyiv region is carried out. The total area of winter wheat fields and winter raps under harvest-2006 has been determined within the indicated region using remote sensing data. It was determined that the total area of winter cultures, identified by using MODIS/TERRA images, differs from that presented in opened information sources by 4–7%. It is shown that satellite data are sensitive to changes of the vegetation covering caused by the tillering of winter cereal crops. It was a background for the determination of the area of winter crops with different growth stage conditions before entering the winter period. The results of the processing of high resolution SPOT XI image were used as reference data for the evaluation of the accuracy of the identification of areas using MODIS/TERRA images. It is proposed to use these methodical approaches for the determination of the area and growing conditions of winter crops for the whole territory of Ukraine.